Pusat Penelitian dan Pengembangan Teknologi Budidaya Pangan Organik di Boyolali(Dengan Pendekatan pada Green Building Futuristic) - Wulandari, Kunthi Nur; , Dr. Ir. Widyastuti Nurjayanti, MT; , Suryaning Setyowati, ST., MT (2016)
Indonesia is known as an agricultural country because most of Indonesian people work in agriculture or farming. Statistical data in 2001 showed that 45% of Indonesia's population works in agriculture. It is based on the fact that this country has a land area of more than 31 million ha which have been ready to be planted. Most of the land can be found in Java Island. Food is a basic human need which continually required. Therefore, food must also be developed in accordance with the growth in population and the development of technology. As an agriculture producing regions, agricultural products that can be used as food in Boyolali district is very diverse. Based on the above Boyolali certainly needs a location that can be used as a research center for the development of organic food technology. However, there is no such a place that is used as the center of all activity in general food processing. All activities include seeding, planting, harvesting, post-harvest processing to the promotion and marketing not well coordinated. Especially as a container and supervision of the processing of organic food. Therefore it is necessary to design a building technology research and development center for organic food technology in the district of Boyolali. The venue is expected to add knowledge to the community, especially in the area of Boyolali about organic food and farming technology. Beside, the place is used for educational tours that focus on organic food crops. In summary, research center for organic food processing development technology is the place for research center and development of organic food cultivation technology, training or workshop hall, for exhibition of organic food, and a place where consumers can get organic food products as well as knowing the treatment process.